A Unusual Case of Epidermoid Cyst in Parotid Gland - Kushaldeep Kaur; Sharma D; Sahni D; Bhagat S; Monga R (GMC Patiala Journal of Research and Medical Education, 2018)
Cystic lesions are common in the head and neck. The most common are the cutaneous cysts, which are referred to as epidermal cysts. These cysts presents as nodular and fluctuant subcutaneous lesions and they are seen most commonly in the acne prone areas like the head, neck and back. They arise following a localized inflammation of the hair follicle and occasionally after the implantation of the epithelium, following trauma or surgery. the presence of benign cystic lesions in the salivary glands is rare. We are presenting a rare case of 30yr old female who presented with a soft swelling on left side of the face. A diagnosis of an epidermoid cyst was given on cytology. Enucleation of cyst was performed and the histopathology confirmed the diagnosis.